PENGARUH AUDIT TENURE, FEE AUDIT, ROTASI AUDIT, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2021-2024) - Etheline Angelica Goldie; Anissa Amaliya Mulya (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of audit tenure, audit fee, auditor rotation, and firm size on audit quality in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research method uses secondary data obtained from the companies’ annual reports. Samples were selected using purposive sampling based on specific criteria, and data were analyzed using logistic regression. The results show that audit tenure has a significant negative effect on audit quality. Meanwhile, audit fee, auditor rotation, and firm size have a significant positive effect on audit quality.